Respon Morfo-Fisiologi Genotipe Kedelai terhadap Naungan Jagung dan Ubikayu - Pratiwi, Herdina; Artari, dan Rina (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2018)
Study on soybeans morpho-physiological responses in artificial or natural shade are beneficial to determine the effects of shade on morpho-physiology and yield of soybean. This research was aimed to study the morpho-physiological responses of soybean varieties under shading of maize and cassava compared to arficial shading. The research was conducted in Kendalpayak Research Station, ILETRI, from February to May 2016 used split plot design with three replications. The main plot was three shade sources: N1:black paranet 50%, N2: maize shade, and N3: cassava shade, while the sub plot was five soybean varieties: Dena 1, Dena 2, Argopuro, Panderman, and Grobogan. Soybean varieties showed morpho-physiology differences depending on the shade source. Soybean grown under shading of cassava had plant height, leaf area ratio, and leaf area lower than under shading of paranet and maize. Cassava shade also caused soybean had higher growth rate, net assimilation rate, and yield than those under paranet and maize shade. Shade-tolerant varieties (Dena 1 and Dena 2) had high yield on all kind of shade. Less tolerant varieties (Panderman and Grobogan) had higher yield under cassava shade and lower yield under paranet and maize shade. Maize crop had similar shade effects with 50% paranet shade.Keywords: Glycine max (L) Merr., intercropping, Manihot esculenta Crantz, paranet, Zea mays L.